Cross-cultural adaptation and psychometric evaluation of the Indonesian Wolf Motor Function Test for stroke rehabilitation - Setiawan Setiawan; Pakaratee Chaiyawat; Jarugool Tretriluxana; Arthorn Riewpaiboon (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: Stroke is a leading cause of mortality and long-term disability worldwide, emphasizing the need for standardized motor assessment tools in rehabilitation. This study aimed to translate and culturally adapt the Wolf Motor Function Test (WMFT) into Indonesian and evaluate its psychometric properties in subacute stroke patients. Methods: A methodological design was employed, consisting of forward translation, back-translation, expert panel review, pretesting, and psychometric evaluation. A total of 25 subacute stroke patients were recruited using purposive sampling. Inter-rater reliability, intra-rater reliability, and internal consistency were assessed using the Intraclass Correlation Coefficient (ICC) and Cronbach’s alpha. Construct validity was examined through correlations with the Fugl-Meyer Assessment for Upper Extremity (FMA-UE). Results: The Indonesian version of the WMFT (I-WMFT) demonstrated excellent reliability. Inter-rater ICC values ranged from 0.895 to 1.000, while intra-rater ICC values ranged from 0.796 to 0.997. Cronbach’s alpha values ranged from 0.799 to 1.000, indicating strong internal consistency. Construct validity was supported by significant correlations with the FMA-UE (r = 0.899 for functional ability and r = −0.828 for movement time), confirming that the I-WMFT accurately reflects upper extremity motor performance. Conclusion: The I-WMFT is a reliable, valid, and culturally appropriate instrument for assessing upper limb motor function in Indonesian subacute stroke patients. Its availability enhances objective clinical evaluation and supports evidence-based rehabilitation practices in Indonesia.